Критерії оцінки суспільної небезпечності особи - Олішевський, О. В.; Olishevskyi, O. V.; ORCID: http://orcid.org/0000-0003-1102-0675 (Вісник Кримінологічної асоціації України. - 2017. - № 3 (17). - С. 105-111, 2017)
Визначено поняття «критерії оцінки суспільної небезпечності особи». Проаналізовано обставини, що характеризують ступінь суспільної небезпечності особи. Класифіковано критерії оцінки суспільної небезпечності особи на обставини об’єктивного та суб’єктивного характерів до, під час та після вчинення злочину. Виділено юридично значущі критерії оцінки суспільної небезпечності особи.

Problem’s setting. There is no concept and relevant criteria of person’s public danger evaluation. Analysis of recent studies. There are several areas of study of an offender person – criminological, criminal law, operative, forensic, psychological and others. All of them together give a single picture of the characteristics of a person. Objective of the research. To define the term ‘criteria of person’s public danger evaluation’ and summarize relevant criteria. Conclusions. Criteria of person’s public danger evaluation are circumstances that characterize her behavior, living conditions, needs, internal mental and volitional processes before, during and after a crime. In other words, these are circumstances of objective and subjective nature before, during and after a crime. The first ones include behavior and living conditions of a person, and to others – personality, internal mental and volitional processes.

Определено понятие «критерии оценки общественной опасности лица». Проанализированы обстоятельства, характеризующие степень общественной опасности лица. Классифицированы критерии оценки общественной опасности лица на обстоятельств объективного и субъективного характеров до, во время и после совершения преступления. Выделено юридически значимые критерии оценки общественной опасности лица.
Criteria of person’s public danger evaluation
Критерии оценки общественной опасности лица
Олішевський, О. В. Критерії оцінки суспільної небезпечності особи / Олександр Володимирович Олішевський // Вісник Кримінологічної асоціації України. - 2017. - № 3 (17). - С. 105-111.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; обставини суспільної небезпечності особи; суспільно небезпечна особа; суспільна небезпечність особи; критерії оцінки суспільної небезпечності особи; evaluation criteria; circumstances; socially dangerous person; person’s public danger; общественно опасная личность; общественная опасность лица